An Investigation of Active Microwave Remote Sensing of Summer Sea Ice in the Western Canadian Arctic - Warner, Kerri (2012)
Active microwave remote sensing is an important tool for classification of sea ice in polar regions. The aim of this research is to improve the understanding of microwave scattering that occurs during the advanced melt season, with a focus on multiyear ice (MYI). This was done using a combination of in situ C-Band scatterometer measurements, geophysical characteristics of ice, and Radarsat-2 data. Results indicate that it is difficult to differentiate between first year ice (FYI) and MYI during advanced melt but combinations of incidence angle and polarization exist that assist with this. It is known that the presence of liquid water governs microwave scattering, therefore further research investigating the variation of microwave backscattered signatures over a diurnal time period was conducted. These results indicate an inverse relationship between temperatures and microwave signatures. The overall results from this research show that summer MYI signatures are extremely variable and difficult to classify. February 2013